EVALUATION OF CLOUD TO GROUND FLASH DENSITY OF 150 KV TRANSMISSION LINE BETWEEN PARIT BARU SUBSTATION AND SENGGIRING SUBSTATIO - Manalu, Ayub Rainaldo; Danial, Danial; Rajagukguk, Managam (Faculty of Engineering, Universitas Tanjungpura, 2024)
SUTT is a high voltage overhead line with a power of 70 kV - 150 kV to distribute electric power from the generating center to the substation or from substation to substation. The purpose of this study was to obtain modeling of lightning strike density on the 150 kV transmission line between Parit Baru substation and Senggiring substation using geostatistical approaches, namely IDW methods (Inverse Distance Weighted). In identifying the level of vulnerability to lightning strikes, Cloud to Ground lightning event data (2018